Myogenesis modelled by human pluripotent stem cells: a multi‐omic study of Duchenne myopathy early onset. Issue 1 (14th February 2021) - Mournetas, Virginie; Massouridès, Emmanuelle; Dupont, Jean‐Baptiste; Kornobis, Etienne; Polvèche, Hélène; Jarrige, Margot; Dorval, Alan R.L.; Gosselin, Maxime R.F.; Manousopoulou, Antigoni; Garbis, Spiros D.; Górecki, Dariusz C.; Pinset, Christian
Abstract: Background: Duchenne muscular dystrophy (DMD) causes severe disability of children and death of young men, with an incidence of approximately 1/5000 male births. Symptoms appear in early childhood, with a diagnosis made mostly around 4 years old, a time where the amount of muscle damage is already significant, preventing early therapeutic interventions that could be more efficient at halting disease progression. In the meantime, the precise moment at which disease phenotypes arise—even asymptomatically—is still unknown. Thus, there is a critical need to better define DMD onset as well as its first manifestations, which could help identify early disease biomarkers and novel therapeutic targets. Methods: We have used both human tissue‐derived myoblasts and human induced pluripotent stem cells (hiPSCs) from DMD patients to model skeletal myogenesis and compared their differentiation dynamics with that of healthy control cells by a comprehensive multi‐omic analysis at seven time points. Results were strengthened with the analysis of isogenic CRISPR‐edited human embryonic stem cells and through comparisons against published transcriptomic and proteomic datasets from human DMD muscles. The study was completed with DMD knockdown/rescue experiments in hiPSC‐derived skeletal muscle progenitor cells and adenosine triphosphate measurement in hiPSC‐derived myotubes. Results: Transcriptome and miRnome comparisons combined with protein analyses demonstrated that hiPSC differentiation (i) leads to embryonic/foetal myotubes that mimic described DMD phenotypes at the differentiation endpoint and (ii) homogeneously and robustly recapitulates key developmental steps—mesoderm, somite, and skeletal muscle. Starting at the somite stage, DMD dysregulations concerned almost 10% of the transcriptome. These include mitochondrial genes whose dysregulations escalate during differentiation. We also describe fibrosis as an intrinsic feature of DMD skeletal muscle cells that begins early during myogenesis. All the omics data are available online for exploration through a graphical interface at https://muscle‐dmd.omics.ovh/ . Conclusions: Our data argue for an early developmental manifestation of DMD whose onset is triggered before the entry into the skeletal muscle compartment, data leading to a necessary reconsideration of dystrophin roles during muscle development. This hiPSC model of skeletal muscle differentiation offers the possibility to explore these functions as well as find earlier DMD biomarkers and therapeutic targets.